2020
DOI: 10.29303/jppipa.v6i1.229
|View full text |Cite
|
Sign up to set email alerts
|

Pemberian Pupuk Silikat dan Pupuk Kandang Terhadap Pertumbuhan, Kadar Brix, dan Hasil Tanaman Sorgum (Sorghum bicolor (L.) Moench)

Abstract: Research on the application of silicate fertilizer and manure to growth, brix level, and yield of sorghum (Sorghum bicolor (L.) Moench) was investigated to find ways to increase sorghum productivity in the dry land. The research method used was an experimental method that was set in a randomized block design consisting of 9 treatments namely control (Si0P0), without silicate and manure, 5 tones/ha (Si0P5), without silicate and manure 10 tones/ha (Si0P10), silicate 100 kg/ha and without manure (Si100P0), silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
1
0
1
Order By: Relevance
“…Reduction of phosphatase activity provides a greater supply of essential high energy required for optimal sugar growth and production. This is in line with the research results of Apliza et al (2020), who concluded that the addition of Si fertilizer could significantly increase the yield and brix content of sorghum.…”
Section: Brix Ratesupporting
confidence: 92%
“…Reduction of phosphatase activity provides a greater supply of essential high energy required for optimal sugar growth and production. This is in line with the research results of Apliza et al (2020), who concluded that the addition of Si fertilizer could significantly increase the yield and brix content of sorghum.…”
Section: Brix Ratesupporting
confidence: 92%
“…Meskipun pada fase awal pertumbuhan, pemberian kompos baglog tidak menujukkan pengaruhnya, namun pada fase generatif pengaruhnya terlihat jelas. Menurut Apliza et al (2020), pupuk kadang mengalami mineralisasi menjadi bentuk hara yang dapat diserap tanaman memerlukan waktu yang cukup lama sehingga tanaman sorgum baru menunjukkan respons pada saat memasuki fase generatif. Pengaruh kompos baglog terbaik (4,55 g) didapatkan dari dosis 30 ton/ha.…”
Section: Pengaruh Urea Dan Kompos Baglog Terhadap Hasil Sorgumunclassified
“…Pengukuran dilakukan pada saat panen adalah hasil hijauan segar tanaman sorgum BMR. Semua sampel sorgum BMR yang sudah dipanen (batang dan daun) kemudian dimasukkan dalam kantong koran (koran sudah diketahui beratnya) sehingga diketahui berat segarnya [2]. Tahap pengambilan data produktivitas tanaman sorgum meliputi pengukuran tinggi tanaman, diameter batang, rasio daun/batang, biomassa segar individu, kadar gula (brix), kandungan bahan kering dan produksi bahan kering (ton/ha).…”
Section: Materi Dan Metode Penelitianunclassified
“…Nilai brix meningkat pada fase pembungaan hingga fase matang fisiologis yang diduga terjadi karena penurunan kandungan air di batang. Selain itu, [11] menambahkan bahwa semakin mendekati umur panen maka kadar gula akan semakin meningkat, dan mengalami penurunan kadar gula setelah melewati masa umur panen akibat aktivitas enzim envertase pada tanaman.…”
Section: Kadar Gula (Brix)unclassified